(untitled) (Studia Prawnicze / The Legal Studies, 1996)
The modification of Article 3(2) of the Anti-trust Act means that licence agreements are treated more liberally compared to other types of agreements. It is privileged that licence agreements are not subject to the prohibitions of the Act both if the restrictions imposed by the agreement are justified and if the restriction of competition caused by the agreement is not substantial; for other types of agreements, exemption from the prohibition is only possible if these circumstances occur together. On the other hand, it is clear from the wording of Article 3(2), which defines the conditions for the application of the Anti-trust Act of 1995 to licence agreements, that the Act only applies to such agreements if their effects in the form of an unreasonable restriction of the parties’ freedom of economic activity and a substantial restriction of competition actually occur. It is therefore about effects already occurring, not potential effects. The purpose of this kind of preference for licence agreements is not clear. The Polish Anti-trust Act should contain a provision introducing a general clause prohibiting cartel agreements that appreciably restrict competition. The absence of such a provision, familiar to the legislations of many countries, deprives our anti-trust law of the necessary flexibility. At the same time, in order to ensure greater certainty of trading, it would be advisable to introduce into our law an institution for examining the compatibility of a concluded contract with anti-trust law. The [anti-trust] law should not include the prohibition of vertical agreements. The prohibition of such agreements is provided for under EC law. It does, however, introduce solutions that allow businesses to be certain about what is allowed and what is prohibited. In the absence of similar solutions (the introduction of the institution of individual exemptions due to the costs involved does not seem possible in our country), the prohibition of vertical agreements undermines the principle of trading certainty. It should also be emphasised that liberalism towards such agreements is supported by the fact that a greater scope of vertical cooperation may contribute to the improvement of trade, which is necessary under the current Polish conditions, and thus to the development of the market and competition. Trade certainty would be served by the introduction of a provision in the Anti-trust Act expressly indicating that agreements between undertakings with an insignificant market share (5-10%) are not subject to the prohibitions provided for therein. The [Anti-trust] Authority should have not the power but the obligation to issue a decision if the conditions set out in [Articles 8(3), 9(1), 11(a)(4)(1) and (2) of the Anti-trust Act] are met. The current structure makes it impossible for the Anti-trust Court to review the Authority’s decisions and means that the Authority is granted too broad a discretion. In contrast, a special standardisation is necessary for those situations in which mergers of companies, despite their restrictive effect on competition, could be deemed to merit authorisation on the grounds of important economic interests. It would be necessary to clearly define in the law what the “permanent restriction of competition” [referred to in Article 12(1) of the Anti-trust Act], which is threatened by the sanction of the demerger, involves. It could be assumed that we are dealing with it, in the broadest terms, when an undertaking persistently evades the implementation of decisions (rulings) ordering the cessation of anti-trust practices. Modyfikacja art. 3 ust. 2 ustawy antymonopolowej oznacza, że umowy licencyjne, w porównaniu z innymi rodzajami umów, traktowane są bardziej liberalnie. Uprzywilejowanie polega na tym, że umowy licencyjne nie podlegają zakazom ustawy zarówno wówczas, gdy wprowadzone przez umowę restrykcje są uzasadnione, jak i wtedy, gdy spowodowane przez umowę ograniczenie konkurencji nie jest istotne; w przypadku innych rodzajów umów zwolnienie od zakazu możliwe jest tylko wtedy, gdy okoliczności te występują łącznie. Ze sformułowania art. 3 ust. 2 określającego warunki zastosowania ustawy antymonopolowej 1995 do umów licencyjnych wyraźnie natomiast wynika, że ustawa ma do tych umów zastosowanie tylko wtedy, gdy ich skutki w postaci nieuzasadnionego ograniczenia swobody działalności gospodarczej stron oraz istotnego ograniczenia konkurencji rzeczywiście występują. Chodzi więc o skutki już występujące, a nie potencjalne. Cel tego rodzaju uprzywilejowania umów licencyjnych nie jest jasny. Polska ustawa antymonopolowa powinna zawierać przepis wprowadzający klauzulę generalną zakazującą porozumień kartelowych, które ograniczają w odczuwalny sposób konkurencję. Brak takiego przepisu, znanego ustawodawstwom wielu państw, pozbawia nasze prawo antymonopolowe niezbędnej elastyczności. W celu zapewnienia większej pewności obrotu należałoby jednocześnie wprowadzić do naszego prawa instytucję służącą badaniu zgodności zawartej umowy z prawem antymonopolowym. Ustawa [antymonopolowa] nie powinna obejmować zakazem porozumień o charakterze pionowym. Zakaz takich porozumień przewiduje prawo WE. Wprowadza ono jednak rozwiązania umożliwiające przedsiębiorstwom uzyskanie pewności co do tego, co jest dozwolone, a co zakazane. Z braku podobnych rozwiązań (wprowadzenie instytucji zwolnień indywidualnych ze względu na związane z nią koszty nie wydaje się u nas możliwe) zakaz porozumień pionowych godzi w zasadę pewności obrotu. Wymaga też podkreślenia, że za liberalizmem wobec tego rodzaju porozumień przemawia to, że większy zakres kooperacji wertykalnej może przyczynić się do niezbędnego w obecnych polskich warunkach usprawnienia handlu, a przez to do rozwoju rynku i konkurencji. Pewności obrotu służyłoby wprowadzenie do ustawy antymonopolowej przepisu wyraźnie wskazującego, że przewidzianym w niej zakazom nie podlegają porozumienia przedsiębiorstw mających nieznaczny udział w rynku (5-10%). Urząd [Antymonopolowy] powinien mieć nie uprawnienie, lecz obowiązek wydania decyzji, jeżeli spełnione zostaną określone w [art. 8 ust. 3, art. 9 ust. 1, art. 11(a) ust. 4 pkt 1 i 2 ustawy antymonopolowej] warunki. Obecna konstrukcja uniemożliwia weryfikację decyzji Urzędu przez Sąd Antymonopolowy i oznacza przyznanie Urzędowi zbyt szerokiego zakresu swobodnego uznania. Szczególne unormowanie jest natomiast konieczne w odniesieniu do tych sytuacji, w których fuzje przedsiębiorstw, mimo ograniczającego oddziaływania na konkurencję, mogłyby być uznane za zasługujące na dopuszczenie ze względu na ważne interesy gospodarki. Należałoby w ustawie wyraźnie określić, na czym polega zagrożone sankcją podziału przedsiębiorstwa "trwałe ograniczenie konkurencji" [o którym mowa w art. 12 ust. 1 ustawy antymonopolowej]. Można by przyjąć, że mamy z nim do czynienia, najogólniej rzecz biorąc, wtedy, gdy przedsiębiorstwo uporczywie uchyla się od wykonywania decyzji (orzeczeń) nakazujących zaprzestanie stosowania praktyk monopolistycznych.